Extra-tumoral breast tissue in breast cancer patients: Variations with steroid contraceptive use - Tone B.Aaman Vamre (2018)
The association between oral contraceptive (OC) use and benign breast changes in extra-tumoral breast tissue was studied histologically in 1,503 breast cancer patients from The WHO Collaborative Study of Neoplasia and Steroid Contraceptives. The occurrence of ductal hyperplasia, ductal atypia, sclerosing adenosis, cysts, apocrine metaplasia, apocrine hyperplasia, apocrine atypia, adenosis, lobular atypia, duct ectasia, calcifications, inflammatory reaction, lactational metaplasia and a high epithelial-stromal ratio was graded semi-quantitatively. Prevalence odds ratio (POR) for each histologic variable was calculated by logistic regression analyses. Patients who had ever used OC had lower occurrence of ductal hyperplasia than never users (POR 0.72 (95% CI 0.52-0.99)). Current use and more than 8 years of use was also associated with a lower prevalence of ductal hyperplasia (POR 0.40 (0.20-0.81) and POR 0.33 (0.17-0.64), respectively). Age > 35 years at first use was associated with increased prevalence of ductal carcinoma in situ (POR 2.15 (1.05-4.40)), but not of atypical ductal hyperplasia. Our results show that the effects of OC use on ductal hyperplasia in non-neoplastic breast tissue of breast cancer patients are similar to what others have found in patients with benign breast disease only. The increased prevalence of extra-tumoral ductal carcinoma in situ in breast cancer patients who started OC use at high age may possibly be explained by a longer preinvasive phase in these patients. © 2005 Wiley-Liss, Inc.